Identification of pyroptosis-related immune signature and drugs for ischemic stroke - Shi, Shanshan; Zhang, Qi; Qu, Changda; Tang, Yushi; Qu, Yewei; Wen, Shirong; Sun, Ruohan; Pan, Yujun (Frontiers in Genetics, 2022)
Background:Ischemic stroke (IS) is a common and serious neurological disease, and multiple pathways of cell apoptosis are implicated in its pathogenesis. Recently, extensive findings have indicated that pyroptosis is involved in various diseases, especially cerebrovascular diseases. Nevertheless, the exact mechanism between pyroptosis and IS is deficiently known. Thus, we aim to investigate the impact of pyroptosis on IS-mediated systemic inflammation. Methods: First, the systematical evaluation of the RNA regulation patterns mediated by 33 pyroptosis-related genes（PRGs）identified in 20 IS samples and 20 matched-control samples was completed. Secondly, a series of bioinformatics algorithms were used to investigate the contribution of PRGs to IS pathogenesis. Then, through the single-variable logistic regression, lasso-cox regression, and multivariable logistic regression analysis, we determined the 3 composition classifiers of PRGs which could distinguish healthy samples from IS samples according to the risk score. Thirdly, by unsupervised consistent cluster analysis in relation to pyroptosis, 20 IS patients were classified. The explorations between pyroptosis and systemic inflammation characteristics were conducted, which was inclusive of immune reaction gene-sets, infiltrating immunocytes, and human leukocyte antigen genes. Results:we identified AIM2,IL1B,and TNF could regulate immuno-inflammatory response after stroke, such as production of inflammatory factors and activation of the immune cells.meanwhile, we finished the identification of distinct expression patterns mediated by pyroptosis, and revealed immune characteristics, Differentially Expressed Genes (DEGs), signaling pathways and targeted drugs under different patterns. Conclusions: Our findings lay a foundation to further research on pyroptosis and IS systemic inflammation, serving for the purpose of improving IS prognosis and its responses to immunotherapy.